Description of The Level of Knowledge and Behavior of Non Health Students In Patients with Pulmonary Tuberculosis - safitri, Selvi; Sukmana, Mayusef; Metungku, Fanny; Khusna, Lailya (Fakultas Kedokteran, Universitas Mulawarman, 2025)
Background: Pulmonary tuberculosis is an infectious disease that remains a major public health issue in Indonesia. It is caused by the Mycobacterium tuberculosis, which attacks the lower respiratory tract. One of the main challenges is the low rate of early detection and poor adherence to treatment. Inadequate knowledge and inappropriate behavior in prevention and transmission further worsen the situation. The public, especially those in the productive age group such as university students, need to increase their awareness of healthy living. Both health and non-health students are expected to act as agents of change by raising awareness and participating actively. This study aims to describe the level of knowledge and behavior of non-health students toward individuals with pulmonary tuberculosis. Method : This study used a quantitative descriptive approach through a survey of 100 non-health students. The sampling technique employed was probability sampling using cluster random sampling. The instrument used was a questionnaire on knowledge and behavior, with data analyzed univariately. Results: A total of 85 respondents (83%) had good knowledge, 16 (16%) had moderate knowledge, and 1 (1%) had poor knowledge. Regarding behavior, 51 respondents (50%) demonstrated good behavior, 14 (14%) moderate behavior, and 37 (36%) poor behavior. Conclusion: Non-health students generally have a good level of knowledge, although their behavior toward individuals with pulmonary tuberculosis still needs improvement. Further education programs and student involvement in public health activities are needed to reinforce positive behavior.